Departmentalization and Organizational Context: The Experience of the University of Guadalajara - Adrián Acosta Silva (Universidad Autónoma de Baja California, 2005)
This work consists of an evaluation of the experience of organizational reform and academic departmentalization at a Mexican public university, the University of Guadalajara (U. of G.), occurred in the period of 1994-2005. It is a research carried out from the perspective of the institutional change analysis, which obeys the interest of carrying out a rigorous evaluation of the process, after 11 years of its institutional operation. From a reconstruction of the context that gave origin and sense to the reform proposal and to the idea of academic departmentalization, some of the results and conditions in which the academic departments of the U. of G operate are analyzed. Finally, some of the problems and challenges that face the departmental structure in this institutional experience are identified.